Tumescent anaesthesia in combination with a femoral nerve block or a sciatic nerve block for surgery of varicose veins - Hillermann, T.; Traber, J. (Phlebologie, 2009)
Tumescent anaesthesia is a widley accepted anaesthetic procedure for the surgery of varicous veins. In our institution tumescent anaesthesia is regularly combined with femoral nerve block or sciatic nerve block for primary operations of the great saphenous vein (GSV) or small saphenous vein (SSV).This combined procedure is described. Retrospective data of 154 operations of the GSV and of 27 operations of the SSV are presented. We used 9.5 mg/kg body weight of prilocain for operations of the GSV and 8.6 mg/kg body weight for operations of the SSV. No serious complications occurred.
Keywords: Tumescent anaesthesia; femoral nerve block; sciatic nerve block; surgery of varicose veins